2014
DOI: 10.1073/pnas.1408993111
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation analysis of single-cell gene expression data reveals epigenetic landscape

Abstract: We present single-cell clustering using bifurcation analysis (SCUBA), a novel computational method for extracting lineage relationships from single-cell gene expression data and modeling the dynamic changes associated with cell differentiation. SCUBA draws techniques from nonlinear dynamics and stochastic differential equation theories, providing a systematic framework for modeling complex processes involving multilineage specifications. By applying SCUBA to analyze two complementary, publicly available datase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
246
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(247 citation statements)
references
References 60 publications
1
246
0
Order By: Relevance
“…Analysis of the data using six independent computational approaches 1,3,4,16,17 resulted in varied delineation of cellular states and intermediates (Supplementary Information, Extended Data Fig. 1-5).…”
mentioning
confidence: 99%
“…Analysis of the data using six independent computational approaches 1,3,4,16,17 resulted in varied delineation of cellular states and intermediates (Supplementary Information, Extended Data Fig. 1-5).…”
mentioning
confidence: 99%
“…To date, several computational methods have been reported that profile developmental processes, such as Monocle (Trapnell et al 2014), Wanderlust (Bendall et al 2014), Wishbone (Setty et al 2016), SLICER (Welch et al 2016), Diffusion Pseudotime , Destiny (Angerer et al 2016), and SCUBA (Marco et al 2014). These methods attempt to order cells into smooth continuous spatiotemporal trajectories to model development.…”
mentioning
confidence: 99%
“…Dimensionality reduction techniques such as principal component analysis and t-distributed Stochastic Neighbor Embedding (t-SNE) shift the interpretation of nonlinearities and cell population clusters to visual inspection of distance-preserving projections of the high dimensional single cell data (5). Besides a first recent systems theory-based attempt to detect bifurcation events from single cell transcriptomics data of developmental processes (10), no constructive and robust approach has been able to objectively describe nonlinear geometries and trajectories for heterogeneous cell populations. Cellular differentiation, in particular, hematopoietic differentiation can follow a nonlinear bifurcated topology (11), where hematopoietic stem cells at the root give rise to a multitude of cellular types through division and differentiation following a branching pattern.…”
Section: Current Methods and Challenges In Analyzing Single-cell Datamentioning
confidence: 99%